Nesting behaviour and breeding success of Willow Tits Poecile montanus in north-west England. Issue 2 (3rd July 2018) - Parry, Wayne; Broughton, Richard K.
ABSTRACT: The British Willow Tit Poecile montanus has undergone a substantial decline in abundance and a severe contraction in range since the 1970s, for reasons that are poorly understood. Breeding failure, due to nest-site competition and predation, has been suggested as a potential factor in the decline, but limited data exist for the nesting ecology and breeding productivity of the species in Britain. We studied a sample of 128 Willow Tit nests in a habitat mosaic of early successional woodland, scrub and wetland in a post-industrial landscape in north-west England, which is increasingly becoming a key refuge for the species in Britain. Results showed that nesting began in April, with standing deadwood of silver birch Betula pendula, common elder Sambucus nigra and black alder Alnus glutinosa being the most frequent nest sites, and the characteristics of nest sites are described. Daily survival rates and overall probability of nest survival are calculated, and details are given for the timing of breeding, clutch size, nestling survival and number of fledglings produced. Overall, 55% of nesting attempts were successful, although many first breeding attempts failed due to Willow Tits being evicted from their nest cavity by Blue Tits Cyanistes caeruleus, or nests being predated by Great Spotted Woodpeckers Dendrocopos major and, potentially, grey squirrels Sciurus carolinensis . Repeat breeding attempts were relatively more successful, but produced fewer fledglings on average. The results are discussed in the context of other studies of Willow Tits and some related species, and also the implications for the conservation of Willow Tits in Britain.